2019
DOI: 10.1155/2019/3815095
|View full text |Cite
|
Sign up to set email alerts
|

Gas Network Development in Compact Bentonite: Key Controls on the Stability of Flow Pathways

Abstract: Compacted bentonite is proposed as an engineered barrier material within facilities for the geological disposal of radioactive waste. Barrier performance and its interaction with a free gas phase must be considered as part of sound repository design. This study involved the long-term experimental examination of gas flow in precompacted bentonite, with particular consideration of gas network stability. Results demonstrate that the stress field experienced by the clay is strongly coupled with gas flow. For the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Consequently, a sharp raise of the gas outflow is observed, mainly fed by gas previously stored in the bottom contact interface and in the crack. Qualitatively similar sharp break-through events were experimentally observed by Horseman et al (1999), Graham et al (2016), Daniels and Harrington (2017), Harrington et al (2017Harrington et al ( , 2019 and Gutiérrez-Rodrigo et al (2021).…”
Section: Gas Injection In a Clay Sample 621 Case Csupporting
confidence: 85%
See 2 more Smart Citations
“…Consequently, a sharp raise of the gas outflow is observed, mainly fed by gas previously stored in the bottom contact interface and in the crack. Qualitatively similar sharp break-through events were experimentally observed by Horseman et al (1999), Graham et al (2016), Daniels and Harrington (2017), Harrington et al (2017Harrington et al ( , 2019 and Gutiérrez-Rodrigo et al (2021).…”
Section: Gas Injection In a Clay Sample 621 Case Csupporting
confidence: 85%
“…From the mechanical point of view, the oscillations are associated to partial closure and reopening of the crack tip. Notably, oscillatory or intermittent outflows after break-through events are also observed experimentally (Graham et al, 2016;Daniels and Harrington, 2017;Harrington et al, 2017Harrington et al, , 2019. Moreover, a detailed analysis of stress perturbation events indicates that the intermittent outflows are correlated with the opening and closing of cracks (Harrington et al, 2019).…”
Section: Gas Injection In a Clay Sample 621 Case Cmentioning
confidence: 70%
See 1 more Smart Citation
“…The results of a series of laboratory experiments in Mx80 bentonite (Cuss et al 2014;Graham et al 2012Graham et al , 2015Harrington et al 2019) and Callovo-Oxfordian claystone (COx) (Cuss et al 2011;Harrington et al 2017a, b) showed that the advective transport of repository gas in bentonite causes the development of new porosity and propagation of dilatant pathways, resulting in the generation and evolution of a gas network. It was also found a strong coupling between stress, gas pressure and flow in bentonite, which takes place during multiple discrete propagation events, demonstrating spatial variability and timedependency of bentonite permeability.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found a strong coupling between stress, gas pressure and flow in bentonite, which takes place during multiple discrete propagation events, demonstrating spatial variability and timedependency of bentonite permeability. Harrington et al (2019) concluded that characterization of the gas network distribution is of fundamental importance in predicting gas dissipation rates and understanding the long-term fate of gas in radioactive waste repositories.…”
Section: Introductionmentioning
confidence: 99%